2013
DOI: 10.1002/star.201300221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation and stearic acid, alone and in combination, on functional, structural, and molecular characteristics of high amylose maize starch

Abstract: The effects of gamma irradiation and stearic acid, alone and in combination, on functional, structural, and molecular characteristics of high amylose maize starch (Hylon VII, ≈60% amylose) were studied. Stearic acid (0, 1.5, and 5%) was added to Hylon VII starch, and then irradiated at 0, 30, and 60 kGy. Gamma irradiation significantly (p ≤ 0.05) increased solubility, water absorption capacity, and oil absorption capacity as well as decreased swelling power (at 90 and 95°C) of Hylon VII starch. These changes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…ALCs enhanced the water and oil absorption capacities of starch flour and decreased the solubility and swelling power of high‐amylose maize starch . Wang et al showed that the swelling power decreased in the presence of ALCs for normal wheat starch, but the decrease varied with lipid type.…”
Section: Effect Of Alcs On the Functional Properties Of Starchmentioning
confidence: 99%
“…ALCs enhanced the water and oil absorption capacities of starch flour and decreased the solubility and swelling power of high‐amylose maize starch . Wang et al showed that the swelling power decreased in the presence of ALCs for normal wheat starch, but the decrease varied with lipid type.…”
Section: Effect Of Alcs On the Functional Properties Of Starchmentioning
confidence: 99%
“…Adding lipids to starch with stirring and heating at 65–75 °C in excess water can form ALCs in an exothermic manner during starch gelatinisation [ 37 ]. The formation of ALCs increases the starch gelatinisation temperature and decreases starch solubility and swelling power [ 38 ]. Some reports suggest that a lipid with an acyl chain length of 14 carbons is efficient for complexation, while others find 16 or 18 carbons to be the preferred acyl chain length [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The X‐ray diffraction (XRD) pattern of the marama root starches and the commercial samples were determined using a PANalytical X'Pert Pro Powder Diffractometer (Eindhoven, The Netherlands) with an X'Celerator detector. The method described by Ocloo et al was used. The operating conditions used for the XRD analyses were: 35 kV and 50 mA; variable divergence and receiving slits using Fe filtered Co‐K α radiation (1.54 Å).…”
Section: Methodsmentioning
confidence: 99%